Bag-1 Silencing Enhanced Chemotherapeutic Drug-induced Apoptosis in MCF-7 Breast Cancer Cells Affecting PI3K/Akt/mTOR and MAPK Signaling Pathways - Akçay, İzzet Mehmet; Dinler Doğanay, Gizem; ARISAN, ELİF DAMLA; KILBAŞ, PELİN ÖZFİLİZ (My University, 2019)
The multifunctional anti-apoptotic Bag-1 protein has important roles in apoptosis, proteasome-mediated degradation, transcriptional regulation, and intracellular signaling. Bag-1 promotes cell survival and proliferation, and is overexpressed in breast cancer. Therefore, Bag-1-targeted therapy might be a promising strategy to treat breast cancer. However, the effects of Bag-1 silencing in combination with conventional chemotherapeutic drugs on cell viability and major signaling pathways have not yet been fully investigated in breast cancer cells. In this study, we investigated the cytotoxic effects of Bag-1 silencing, alone and in combination with cisplatin or paclitaxel treatment, in MCF-7 breast cancer cells. Bag-1 knockdown by shRNA or siRNA transfection sensitized MCF-7 cells to apoptosis induced by cisplatin or paclitaxel. Combination of Bag-1 silencing and drug treatment more potently downregulated the pro-survival PI3K/Akt/mTOR and p44/42 mitogen activated protein kinase (MAPK) pathways, and more potently upregulated the stress-activated p38 and SAPK/JNK MAPK pathways. Bag1-silenced drug-treated cells had also highly reduced proliferative capacity, downregulated cyclin–cyclin dependent kinase complexes and upregulated tumor suppressors p21 and Rb. These results overall indicated that Bag-1 silencing enhanced cisplatin- or paclitaxel-induced cytotoxicity through multiple pathways. In conclusion, Bag-1 targeted therapy might enhance the therapeutic potential of conventional anti-cancer drugs in the treatment of breast cancer.
Keywords: Bag-1 siRNA/shRNA; Chemotherapeutic Agents; Apoptosis; Breast Cancer; MAPK · PI3K/Akt/mTOR Pathway